Сезонные изменения содержания витамина А в печени серой полевки (Microtus arvalis Pall.) - Золотухина, С.И. (Вестник зоологии, 1968)
The author studied the content of vitamin A in liver of Microtus arvalis P a l l. during various seasons of the year. A change is found in the content of vitamin A (axerophthol) during the year which is, probably, connected with a physiological state of ani-mals and with the food conditions in various seasons of the year. Remove selected